The Potential Use of Liposomes as a Lipid Supplement in the Culture of Juvenile Crassostrea gigas - Hasanat, M.A.; Sarkar, M.S.A.; Jahan, Parveen; Uddin, Musleh; Lavens, Patrick (Asian Journal of Chemistry, 2010)
Hatchery reared Crassostrea gigas were grown for 4 weeks by feeding with Tetraselmis suecica at a ration of 0.5%, 1.0% and 1.5% algae (dry weight) per weight per day. The control diet was a mixture of lsochrysis galbana (Clone T-Iso) and T. suecica (1 : 1 on dry weight basis), which is known to support good growth. T. suecica is deficient in docosahexaenoic acid [22 : 6 (n-3)] but is rich in eicosapentaenoic acid [20 : 5 (n-3)]. The use of liposomes and emulsions as a fatty acid delivery system for the supplementation of a T. suecica diet for juvenile C. gigas was investigated. In addition, the effect of the artificial diets on the growth of C. gigas and their possible effect on the bacterial loading in the culture water was followed. The addition of the liposomes did not enhance the growth. The liposomes or emulsions were probably too small to be efficiently ingested by the spat. The number of bacteria was slightly higher in the culture water where liposomes or emulsions were used as lipid supplement. The slow evolution rate of the bacterial loading indicated that the oysters might ingest bacteria but this had no significant effect on their growth.